Hiszpański romans rycerski w sieci - Setkowicz, Katarzyna (Zagadnienia Rodzajów Literackich, 2020)
In 16th-century Spain, the romances of chivalry were one of the pillars of the publishing industry. Today, however, they remain little known to both the general public and literary researchers who rediscovered them just a few decades ago. The special situation of the romances of chivalry means that on the one hand, it is a genre that, along with the development of digitization technology, can receive a second life, and on the other — it poses particular challenges for the researchers. The process of optical character recognition in antique prints with typical editorial characteristics of Spanish romances cannot yet be carried out automatically. Hence, the search for solutions that will bring the reader closer to the content of old print, and the researcher — to carry out research based on text mining. The purpose of the article is to show attempts to introduce Spanish chivalric romance into the Internet space, undertaken in various academic centres, as well as to outline possible perspectives for further actions in this field.